Выражение „голосовать ногами / głosować nogami” в современном русском и польском языках - Jolanta Miturska-Bojanowska; Jolanta Ignatowicz-Skowrońska (Studia Rossica Posnaniensia)
Since the end of the 20th century, in the Russian and Polish language the phrase голосовать ногами / głosować nogami has broadened its usage and its meaning  in both languages. This refers to the primal Latin phrase pedibus in sententiam ire.  Its popularity could be related to the influence of the English idiom vote with your feet.